Comparison of ultraviolet B-induced cutaneous inflammation and skin pathergy test in Behçet's disease. (April 2013) - Sayarlioglu, Mehmet; Kamali, Sevil; Cefle, Ayse; Inanc, Murat; Ocal, Lale; Aral, Orhan; Konice, Meral; Gul, Ahmet
Background: Nonspecific hyper-reactive inflammatory response is an important feature of Behçet's disease (BD), but the underlying mechanism has yet to be identified. Ultraviolet B (UVB)-induced erythema is a well-established experimental method for the investigation of antigen-independent cutaneous inflammation, and no data are available on UVB response in BD patients.Aim: To investigate the UVB-induced erythema by determining the minimal erythema dose in BD patients and matched healthy controls, and also to compare the results of UVB response with the skin pathergy reaction.Patients & methods: The study group consisted of 47 patients with BD, 32 with various rheumatic diseases and 21 healthy volunteers. UVM-57 (Ultraviolet Products, Cambridge, UK; 302 nm), was used as the narrow-band UVB source. The forearm of each individual was exposed to a 0.14–10.45 J/cm 2 dose of 302-nm UVB with 0.045 J/cm 2 increments. The skin pathergy reaction was tested using a 20 G hypodermic needle as previously described. The erythema and skin pathergy reaction were observed at 24 and 48 h.Results: The mean minimal erythema dose and minimal erythema dose duration in BD patients was found to be lower than those in controls, and the difference was statistically significant between BD patients and diseased controls at 48 h (0.27 ± 0.08 vs 0.32 ± 0.07 J/cm 2 ; and 2.95 ± 0.92 vs 3.5 ± 0.07 min, respectively; p = 0.032 for both), and between BD and combined (diseased plus healthy) control groups at 24 h (0.24 ± 0.09 vs 0.29 ± 0.07 J/cm 2 and 2.76 ± 0.82 vs 3.18 ± 0.75 min, respectively; p = 0.036 and p = 0.05, respectively) and 48 h (0.27 ± 0.08 vs 0.31 ± 0.07 J/cm 2 and 2.95 ± 0.92 vs 3.38 ± 0.75 min, respectively; p = 0.039 for both). This difference becomes more prominent when patients and controls with the same skin color (type 3) were compared. Conclusion: The development of a cutaneous erythematous response with significantly lower doses of UVB further supports the nonspecific hyper-reactive inflammatory characteristics of BD and suggests that it can be induced without any antigen. These preliminary results may help in understanding the cutaneous inflammation in BD and developing alternative methods to investigate it.